Unity of law and legal act as a key principle of the rule of law - Gilmullin, Ainur Razifovich; Krasnov, Eduard Vladimirovich (Cuestiones Políticas, 2020)
This article discusses one of the key principles of the rule of law, such as the principle of unity of law. Consequently, the opinions of scholars who define this principle were a naturalized and their main characteristics stand out. In addition, the article provides an attempt to compare the principle of unity of law with the principles of the rule of law and highlight its general characteristics and differences. In methodological terms, the technique of documentary research and comparative hermeneutics was used. It is concluded that the categories of "rule of law" are understood by several authors very differently, there is no consolidation in the definition of this concept; often the above principles contradict each other: they express the static or dynamics of the rule of law, so they require additional doctrinal legal awareness and study. Under modern  socio-political conditions, it would be better to use unity of law as the principle of the rule of law; because, it is the principle of unity of law that can provide effective and rational protection and realization of the rights and freedoms of  citizens, societies and states.